The Role of Religious Affairs Office (KUA) of Makassar City in Preventing Marriage Violation under the Maṣlaḥah Mursalah Principle - HM, Muhajir; Hasan, Hamzah; Supardin, Supardin; Fikri, Mursyid; Shesa, Laras (al-'adalah, 2024)
This study discusses the role of the Makassar City Religious Affairs Office (KUA) in preventing marital violations based on the principle of maṣlaḥah mursalah. The aim is to obtain a complete picture of the position of the Religious Affairs Office (KUA) as the front guard in resolving various problems and marital violations in the community. This study is qualitative using a descriptive phenomenological approach. Data were obtained from two types of sources, namely primary sources and secondary sources. Primary sources are carried out through interviews, observations, and documentation whereas secondary sources are in the form of certain documents, standard books, articles, or other materials related to the topic studied. Interviews were conducted with the Head of KUA, Penghulu, and office staff. This study involved five KUA in Makassar City with a case study approach that was analyzed in depth through the principle of maṣlaḥah mursalah. This study found that the KUA in Makassar City has played an active role in taking various strategic steps to realize flexible marriage law policies that are in line with the dynamics and needs of society. Other policies that have also been implemented include the formation of a special team, the implementation of routine studies on Islamic marriage law, and increasing cooperation with research institutions. This policy is implemented to make marriage law relevant and responsive to social change. All of this is evidence that in addition to being a public service institution, the KUA in Makassar has also played a role in maintaining legal flexibility so that it remains in line with the interests of the wider community.